Perceived Social Support as a Predictor of Mental Health among First-Year College Students at a State University - Fronda, Mhyanna; Villegas, Khrisha; Bacani, Michelle Anne; Coronado, Eunice; Rivera, Charlene; Vergara, Jerald; Gaddi, John Angelo; Popatco, Eugene Byron (Journal of Interdisciplinary Perspectives, 2025)
The perceived support from family, friends, and peers plays a critical role in helping students navigate the challenges of university life. Strong social support is shown to alleviate stress and improve overall well-being. In contrast, insufficient support is linked to poorer mental health outcomes. While existing research has explored the general link between social support and well-being, the specific ways perceived social support predicts mental health outcomes among first-year college students have not been thoroughly studied locally. This study highlights how perceived social support predicts first-year students' mental health, which can be used to develop targeted counseling support interventions. This quantitative study utilized a predictive correlational design to investigate the relationship between perceived social support and mental health among first-year college students (n=104) at a state university in Pampanga, Philippines. The sample size was determined through G*Power 3.1.9.7, and the respondents were selected using a purposive sampling technique. Data analysis using JAMOVI version 2.4.14 revealed a weak and negative connection (p. < 0.001, R=-0.48) between perceived social support and mental health among first- year college students. Furthermore, the data demonstrated that first-year college students' mental health can be predicted by 23% of perceived social support. The findings indicate that while perceived social support can benefit some, excessive support can lead to distress, psychological suffering, hindered autonomy, and weakened stress-coping abilities. Perceived support from a demanding family environment can decrease mental health outcomes among first-year college learners. Stressor type and support provider characteristics may influence this negative association. The importance of perceived social support in predicting mental health emphasizes the need for supportive environments that increase mental well-being among first-year college students.